ErbB4 in Laminated Brain Structures: A Neurodevelopmental Approach to Schizophrenia - Perez-Garcia, Carlos G. (Frontiers in Cellular Neuroscience, 2015)
The susceptibility genes for schizophrenia Neuregulin-1 (NRG1) and ErbB4 have critical functions during brain development and in the adult. Alterations in the ErbB4 signaling pathway cause a variety of neurodevelopmental defects including deficiencies in neuronal migration, synaptic plasticity and myelination. I have used the ErbB4-/- HER4heart KO mice to study the neurodevelopmental insults associated to deficiencies in the NRG1-ErbB4 signaling pathway and their potential implication with brain disorders such as schizophrenia, a chronic psychiatric disease affecting 1% of the population worldwide. ErbB4 deletion results in an array of neurodevelopmental deficits that are consistent with a schizophrenic model. First, similar defects appear in multiple brain structures, from the cortex to the cerebellum. Second, these defects affect multiple aspects of brain development, from deficits in neuronal migration to impairments in excitatory/inhibitory systems, including reductions in brain volume, cortical and cerebellar heteropias, alterations in number and distribution of specific subpopulations of interneurons, deficiencies in the astrocytic and oligodendrocytic lineages, and additional insults in major brain structures. This suggests that alterations in specific neurodevelopmental genes that play similar functions in multiple neuroanatomical structures might account for some of the symptomatology observed in schizophrenic patients, such as defects in cognition. ErbB4 mutation uncovers flaws in brain development that are compatible with a neurodevelopmental model of schizophrenia, and it establishes a comprehensive model to study the basis of the disorder before symptoms are detected in the adult.